Recursos de escalabilidade e alta disponibilidade para aplicações web - Gregol, Régis Eduardo Weizenmann (2011)
With the expansion of the technology and increasing access to existing applications on the Internet, it becomes a challenge to keep them available all the time. This work aims to demonstrate in theory and in practice the use of resources to scale a Web application and get the same high availability. Such features can be applied directly to the application as the use of Ajax but can also be applied to server architecture that will provide the application and can use concepts of vertical scalability, clustering, and horizontal scalability. Furthermore, demonstrate techniques to increase Web application performance.